3‐(3‐Hydroxyphenyl)‐Propionic Acid (PPA) Suppresses Osteoblastic Cell Senescence to Promote Bone Accretion in Mice. (23rd August 2019) - Chen, Jin‐Ran; Wankhade, Umesh D; Alund, Alexander W; Blackburn, Michael L; Shankar, Kartik; Lazarenko, Oxana P
ABSTRACT: Phenolic acids (PAs) are metabolites derived from polyphenolic compounds found in fruits and vegetables resulting from the actions of gut bacteria. Previously, we reported that the levels of seven individual PAs were found to be at least 10 times higher in the serum of rats fed a blueberry (BB)‐containing diet compared to those fed a control diet. We have characterized the effects of one such BB‐associated serum PA, 3‐(3‐hydroxyphenyl)‐propionic acid (PPA), on senescence signaling and promotion of mesenchymal stem cell differentiation toward osteoblasts, while suppressing adipogenesis in the stem cells. To better understand the mechanistic actions of PPA on bone formation in vivo, we administered four doses of PPA (0.1, 0.5, 1, and 5 mg/kg/day; daily i.p.) to 1‐month‐old female C57BL6/J mice for 30 days. We did not observe significant effects of PPA on cortical bone; however, there were significantly higher bone volume and trabecular thickness and increased osteoblastic cell number, but decreased osteoclastic cell number in PPA‐treated groups compared to controls. These morphological and cellular outcomes of bone were reflected in changes of bone formation markers in serum and bone marrow plasma. PPA treatment reduced senescence signaling as evaluated by senescence‐associated β‐galactosidase activity, PPARγ, p53, and p21 expression in bone. In conclusion, PPA is capable of altering the mesenchymal stem cell differentiation program and bone cell senescence. This raises the possibility that BB‐rich diets promote bone growth through increasing systemic PAs, a question that merits additional investigation. © 2019 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.